Song of the Babaylan living voices, medicines, spiritualities of Philippine ritualist-oralist-healers - Nono, Grace (Quezon City Institute of Spirituality in Asia, 2013)
On the babaylan, a Visayan term identifying an indigenous Filipino religious leader, who functions as a healer, a shaman, a seer, and a community "miracle-worker" or a combination of any of those.
In English. Songs in their original dialects with English translation.
Keywords: Music -- Philippines -- History and criticism; Healers -- Philippines -- Music; Women shamans -- Philippines -- Music; Rites and ceremonies -- Philippines; Folk songs -- Philippines -- Texts; Philippines -- Folklore